ENSURING ELECTROMAGNETIC SAFETY OF THE PRODUCTION ENVIRONMENT - Honcharova, Olha; Yu , Qiang; Goncharov, Pavlo (Collection of scientific papers «ΛΌГOΣ», 2024)
Machinery manufacturing is a component of the hardware industry and plays an important role in China’s economic construction. The manufactured equipment is a source of electromagnetic fields of different frequencies. Electromagnetic fields are one of the factors of negative impact on human health and surrounding equipment.